Managing Enterprise Data Complexity Using Web Services Part 2 Developing enterprise digital dashboards using data services architecture. - Ganesh, Dr. Jai (SOA webservices journal.)
Enterprises are increasingly feeling the need for shorter lead time for decision making, the need to extract and present KPI (Key Performance indicators) to management, and the need for enhanced response capability. These business needs are not in sync with the technological challenges such as the presence of heterogeneous technologies and disparate enterprise systems (e.g. ERP, SCM, CRM, etc.). This situation gets complicated with the increasing number of merges and acquisitions resulting in the various business units within an enterprise having their own data warehouses. Adding to this is the increasing number of users inside and outside the enterprise who need real-time access to information.